Hyperactivity, perseveration and increased responding during attentional rule acquisition in the Fragile X mouse model - Kramvis, Ioannis; Mansvelder, Huibert; Loos, Maarten; Meredith, Rhiannon (Frontiers in Behavioral Neuroscience, 2013)
Attentional deficits and executive function impairments are common to many neurodevelopmental disorders of intellectual disability and autism, including Fragile X syndrome. In the knockout mouse model for Fragile X syndrome, significant changes in synaptic plasticity and connectivity are found in the prefrontal cortex – a prominent region for attentional processing and executive control. Given these alterations in prefrontal cortex synaptic function, we tested whether adult Fragile X knockout mice exhibited corresponding impairments in inhibitory control, perseveration and sustained attention. Furthermore, we investigated individual performance during attentional rule acquisition. Using the 5-choice serial reaction time task, our results show no impairments in inhibitory control and sustained attention. Fragile X knockout mice exhibited enhanced levels of correct and incorrect responding, as well as perseveration of responding during initial phases of rule acquisition, that normalised with training. For both knockout and wild type mice, pharmacological attenuation of metabotropic glutamate receptor 5 signalling did not affect response accuracy but reduced impulsive responses and increased omission errors. Upon rule reversal, Fragile X knockout mice made more correct and incorrect responses, similar to the initial phases of rule acquisition. Analogous to heightened activity upon novel rule acquisition, Fragile X knockout mice were transiently hyperactive in both a novel open field arena and novel home cage. Hyperactivity ceased with familiarisation to the environment. Our findings demonstrate normal inhibitory control and sustained attention but heightened perseveration, responding, and hyperactivity during novel rule acquisition and during exposure to novel environments in Fragile X knockout mice. We therefore provide evidence for subtle but significant differences in the processing of novel stimuli in the mouse model for the Fragile X syndrome.